Applikasi Turbin Cross-Flow untuk Pembangkit Listrik Tenaga Mikrohidro di Kalimantan Barat - Arsyad, M. Iqbal (ELKHA : Jurnal Teknik Elektro, 2009)
Abstract The best geographical areas for exploiting small scale hydro power are those where there are steep rivers flowing all year round, the hill areas of countries with high year-round rainfall, or the great mountain ranges and their foothills. Islands with moist marine climates, such as the Indonesia is suitable. Low-head turbines have been developed for small-scale exploitation of rivers where there is a small head but sufficient flow to provide adequate power. A turbine converts the energy in falling water into shaft power. Cross-Flow turbine is meant for those purposes with low head. In this paper we introduce the practical aspects of cross-flow turbine for application be possible, especially the calculation of potential power to some rivers in Kalimantan Barat. Keywords Cross-flow turbine, practical aspects, Kalimantan Barat, micro-hydro power plant.